Rancang bangun aplikasi informasi pengelolaan keamanan berbasis web - Triyono Andik Priyanto; Sharyanto Sharyanto; Joseph Joseph (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The building security system is a man-made tool based on technological developments that is useful for helping humans in critical conditions to maintain security in buildings such as fire, theft, and natural disasters that can cause damage and there is no sense of comfort in buildings, both apartments, shop houses, offices, malls, and so on. Based on problems that often occur about the insecurity of a building, for example the danger of fire that often occurs, and theft. The problem at the Directorate General of EBTKE is related to the absence of a security management system at the Directorate General of EBTKE so that fires and thefts often occur because of the absence of a security-based system. In order to collect the required data, several methods are used that can help. Security management which is still manual is replaced by using a computerized process. This will increase the effectiveness and efficiency of work as well as produce better and faster information to those who need it. As for the following details, the system that was running previously still in paper form did not have data storage in the form of a database, so that the data storage process was more difficult to find, so it was proposed to improve the current security management system.